Advancing parameter estimation with Characteristic Finite Difference Method (CFDM) for a marine ecosystem model by assimilating satellite observations: Spatial distributions - Xu, Minjie; Liu, Yongzhi; Zhao, Zihan; Fu, Kai; Lv, Xianqing (Frontiers in Marine Science, 2022)
The ecosystem parameters are critical for precisely determining the marine ecological process and improving the simulations of the marine ecological model. In this study, based on the NPZD (nutrient, phytoplankton, zooplankton and detritus) model, the surface chlorophyll-a observations obtained from Sea-viewing Wide Field-of-view Sensor (SeaWiFS) data were assimilated to estimate spatially ecosystem parameters using an adjoint assimilation method with characteristic finite difference scheme in the Bohai, Yellow, and East China Seas. The experiments of the moving Gaussian hump indicated that the characteristic finite difference method (CFDM) can get rid of the limit of stability to using large time steps and reduces long computation durations and large memory requirements. The model performance was significantly improved after data assimilation with CFDM using a large time step of 6 hours. Moreover, the distributions of parameters of the NPZD model in winter in the Bohai Sea, the Yellow Sea, and the East China Sea were simulated by our method. Overall, the developed method can efficiently optimize the ecosystem parameters and the results can be beneficial for determining reasonable parameters of the marine ecological model.